Bone Density and Bone Geometry in University Athletes From Sports With Different Levels of Impact: Simultaneous Association With Multiple Factors - Moraes, Mikael S.; Fernandes, Rômulo A. [UNESP]; Moreno, Yara M.F.; Pelegrini, Andreia; Silva, Diego A.S. (Wolters Kluwer, 2022)
Moraes, MS, Fernandes, RA, Moreno, YMF, Pelegrini, A, and Silva, DAS. Bone density and bone geometry in university athletes from sports with different levels of impact: simultaneous association with multiple factors. J Strength Cond Res 36(11): 3113-3121, 2022 - The aim of this study was to use the bone loading unit (BLU) classification to compare bone density and bone geometry of sports with different levels of impact, simultaneously controlling the multiple factors that interfere with bone metabolism in athletes. Overall, 167 university athletes (92 men) participated in the study. Bone mineral density (BMD), strength index, cross-sectional area (CSA) at the moment of inertia, section modulus (Z), CSA, neck-shaft angle (NSA), and hip axis length (HAL) were measured. Sports were categorized by level of impact, high BLU (higher impact) and moderate/low BLU (lower impact). Covariates were fat mass, lean tissue mass, training volume, time of practice, dietary supplementation, use of oral contraceptives and menstrual status. Multiple linear regression with 5% significance level (p < 0.05) was used. In men, HAL was higher in sports with high BLU compared with those with moderate/low BLU (β: -0.21; R2: 0.30; p = 0.03). In women, NSA was higher in sports with moderate/low BLU compared with those with high BLU (β: 0.31; R2: 0.11; p = 0.02). There was no difference between BLU groups for BMD. These results persisted when the simultaneous interference of covariates was controlled. Thus, this study recommends BLU to classify sports and reinforces the importance of monitoring HAL and NSA in athletes in addition to the control of multiple factors that interfere with bone metabolism, because they influence physical performance and bone health during and after athletic life.
Keywords: athletic performance; body composition; bone remodeling; nutritional sciences of sport